Impaired airway epithelial miR-155/BACH1/NRF2 axis and hypoxia gene expression during RSV infection in children with down syndrome - Welham, Allison; Chorvinsky, Elizabeth; Bhattacharya, Surajit; Salka, Kyle; Bera, Betelehem Solomon; Admasu, Woudasie; Straker, Maria C.; Gutierrez, Maria J.; Jaiswal, Jyoti K.; Nino, Gustavo (Frontiers in Pediatrics, 2025)
BackgroundChildren with Down Syndrome (DS) are at high risk for severe respiratory syncytial virus (RSV) infections. DS is associated with impaired cellular responses to oxidative stress and hypoxia; however, these abnormalities have not been explored in trisomy 21 (TS21) airway epithelial cells (AECs) during RSV infection. Understanding these defects is key to identifying factors contributing to severe RSV infections in this high-risk group.MethodsAECs from children with and without DS were analyzed at baseline and after RSV infection to assess NRF2-induced protective genes against oxidative stress and hypoxia, including the enzyme heme oxygenase 1 (HO-1). To investigate DS-specific defects, we focused on miR-155 and BACH1, which regulate NRF2 signaling and HO-1 expression, and are both encoded on chromosome 21. RNA-seq analyses were performed to examine genome-wide hypoxia-related gene responses in control and TS21 AECs at baseline and after RSV infection.ResultsOur findings show that miR-155 inhibits BACH1, leading to increased NRF2-driven HO-1 expression in euploid AECs. In contrast, TS21 AECs from children with DS exhibited impaired HO-1 induction following miR-155 treatment. This was attributed to reduced transcription of the HMOX1 gene, which encodes HO-1, along with global downregulation of hypoxia response genes in DS at baseline and after RSV infection in TS21 AECs.ConclusionsSevere RSV infections in children with DS may be linked to intrinsic defects in AEC responses to hypoxia, including NRF2-driven cytoprotective enzymes like HO-1. These findings offer new mechanistic insights into RSV pathophysiology and potential therapeutic targets in children with DS.